Estudio de viabilidad financiera para la creación de una sucursal de la empresa Ecoplast2k, productora de postes a base de plásticos reciclados implementando el modelo de economía circular (2023)
The purpose of this work is to study the financial feasibility of setting up an ECOPLAST2k plant for the production of recycled plastic poles in a branch office. All this directed to the agro-industrial industry sector, according to the company's guidelines. Initially it was necessary to make an introduction to the circular economy and to know the advantages and benefits of implementing this model for the development of the study. The star product is the 8x8 recycled plastic-based post, since it is the most used in the agricultural sector and, given the volume of sales, it allows strengthening the circular economy theme in the company ECOPLAST2k. Therefore, it was important to know and identify which plastics are involved in this chain, thus confirming which are viable for the development of the product and the method to be implemented in the new branch. In relation to the above, a field visit was made to the company ECOPLAST2k, where the process of making poles from recycled plastic was described in a process diagram. They were described through a technical sheet of the machinery required for the assembly of the circular economy processes of plastic waste. Given this development it is important to describe the BOM, which define the materials to carry out the process of elaboration of a piece of recycled plastic (Post). All this was done in order to know how much material was needed to be able to execute the feasibility study. Performing this type of requirements and analysis is of utmost importance because it helps the development of the financial feasibility study, where costs, labor, and administrative expenses that will be evidenced in the document were revealed.